PEMBIARAN PERILAKU MEROKOK PADA ANAK SEBAGAI PELANGGARAN HAK ASASI ANAK UNTUK TUMBUH DAN KEMBANG SECARA SEHAT - Benget Hasudungan Simatupang (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Children's rights are guaranteed in Constitution to grow in Article 28B paragraph 2. Teenage smokers in Indonesia are increasing every year. They are generally produced from parents or environmental smokers. This is a threat to the nation's next generation because smoking behavior causes health problems and acute illness. This research method is normative legal research with an approach to statutory regulations related to children's human rights to grow and develop in a healthy and optimal manner. The law does not clearly regulate protection so that children avoid smoking behavior but in Government Regulation Number 109 of 2012 concerning the Security of materials containing addictive substances in the form of tobacco for health there are special provisions so that a child (under 18 years) and pregnant women protected from addictive substances in the form of prevention activities, restoration of physical and mental health and social recovery. Factors that can encourage a child to become an active smoker are usually determined by the environment in which the child grows and develops. Such as easy access for someone to get cigarettes at relatively cheap prices and influence from peers or unhealthy associations. Efforts that can be made so that children avoid smoking behavior really need the participation of parents in taking the right approach for their children and firm action from the government in taking action against violators of provisions in laws and regulations. it is necessary to strictly regulate the prohibition of active smoking behavior towards children in a law with a rehabilitation paradigm.Keywords: Child Smoking Behavior, Human rights violations, Healthy Growth.